Degree assortativity in collaboration networks and invention performance - Khanna, Rajat; Guler, Isin (Strategic Management Journal, 2022)
Abstract Research Summary We investigate the implications of the degree assortativity of intra‐firm networks for firms' innovation performance. We argue that prevalent patterns of collaborative relationships between organizational members can lead to variations in the levels of degree assortativity in intra‐firm networks, ranging from disassortative structures (highly central members connect with peripheral members) to assortative ones (highly central members connect with other highly central members and vice versa). These patterns influence knowledge access and resource mobilization pathways and are thus associated with various firm‐level invention outcomes. Using coarsened exact matching methodology and controlling for other characteristics of the intra‐firm network structures, we find that assortative structures in the pharmaceutical industry are associated with larger invention output, but inventions originating from assortative structures have lower average novelty and impact. Managerial Summary A central challenge in knowledge‐based industries is the design of collaborative teams to increase innovative output. In this article, we show that firms in the pharmaceutical industry vary in the extent to which central inventors within a firm collaborate with peripheral inventors. Further, the ideal composition varies based on the desired innovative output: Firms with frequent collaborations between central inventors have higher inventive productivity, while firms with higher mixing between central and peripheral inventors generate inventions that are on average more novel and have higher impact. Results have implications for organizational design toward desired innovative outcomes, as well as management of strategic human capital.